An Empirical Estimation of Asia's Untapped Regional Integration Potential Using Data Envelopment Analysis - Dominik Naeher (Asian Development Bank (ADB), 2015)
This paper uses directed bilateral flow data on multiple dimensions of economic integration to construct a composite index of regional integration outcomes covering 19 regions in various parts of the world. As a first step, the multidimensional indicator is used to rank regions according to their current degree of regional integration, which allows for a direct comparison of Asia's regional integration performance with those of other regions of the world. As a second step, the constructed indicator of regional integration outcomes is used as the output variable in a data envelopment analysis (DEA) to estimate Asia's untapped regional integration potential.
hdl:11540/5113
Keywords: F02; F10; F13; F15; 330; Asia; composite index; data envelopment analysis; integration potential; regional integration